(3GdQhVI GdSdjeGfjI aj edhc GdOhdI GdESeGYjdjI (B[(3HGdeZQH(B] (3hef JbOegG ef GdOhd GdESdGejIs - (3JPjjd HdbGSe Hf CMeO Hf Ydj Hf EHQGgje GdRjGfis ((3GdMSf Hf GdMSfi GdEOQjSi Gdefhfi s)
(3ChdgG (B:s
(3GdMeO ddg Ndb GdEfSGf h aVdg JaVjdG , haVdg Ydi SGFQ GdMjhGf LedI hJaUjdG s
(3BNQgG (B:s
(3Ydjc SdGe jedC GdLh eScg hjQRi HQhV GdRgQ eG WdY GdfLe s
(3GfXQ agQS GdeNWhWGJ GdYQHjI GdeMahXI ai GdNRGfI GdYGeI HQHGW GdaJM HGdeZQH GdCbUi (B2/137s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B172s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B880 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B214 s
Keywords: (3GdJGQjNs